Effectiveness of social skills training on behavioral problems and social skills in high-functioning adolescents with autism spectrum disorder (ASD) - سعید صادقی (فصلنامه روان‌شناسی کاربردی, 2017)
Aim: The aim of this study was to determine the effectiveness of social skills training on problematic behaviors and social skills in adolescents with high-function autism spectrum disorder. Method: The study method was quasi-experimental with pre–post-test and follow-up without control group and the population included 60 adolescents between 11 & 17 years old who were clients of Tehran Autism Center and Ava Autism Center in Tehran. By using purposeful sampling, twelve adolescents with H-F ASD were selected and divided into two equal groups of six persons who participated in 10 sessions of 90-minute intervention and received two sessions per week. Then their parents completed the Gresham and Elliott Social Skills Rating Scale-Version parents (1990) at pre, posttest and follow up. Data was analyzed using repeated measures analysis of variance. Results: Results showed that participating in intervention sessions lead to increased adolescents social skills, including cooperation (F=9.92,P=0.005), assertiveness (F=7.81, P=0.009), responsibility (F=8.18، P=0.002) and self-control (F=7.64, P=0.003); but this effect in one-month follow-up phase was not stable, on the other hand, no significant differences were found in participants' external (F=0.28, P=0.75) and internal (F=0.24, P=0.65) behavioral problems and over-activity (F=1.08, P=0.33). Conclusion: Based on these findings, social skills training programs can be consider an effective method for improving social skills of adolescents with high-functioning autism spectrum disorder and it may be suggested that these methods could be applied in order to improve social skills of young people. However, to keep persistence of effectiveness, more practice in natural life environment is necessary and also as far as reduction of problematic behaviors and identify effective interventions are concerned, more research is certainly needed.